Elasticity, plasticity and fracture toughness at ambient and cryogenic temperatures of epoxy systems used for the impregnation of high-field superconducting magnets. (April 2021) - Brem, André; Gold, Barbara J.; Auchmann, Bernhard; Tommasini, Davide; Tervoort, Theo A.
Highlights: Experimental protocol to measure yield stress of epoxies at cryogenic temperatures. Rate-dependent yield stress of epoxies at room temperature follows Eyring theory. No rate-dependence of the yield stress of epoxies at cryogenic temperatures. At cryogenic temperatures all epoxies have similar elastic and plastic properties. The fracture toughness of epoxies at cryogenic temperatures is vastly different. Abstract: This study evaluates the thermal expansion coefficient, as well as the elastic-, plastic- and fracture behaviour, at ambient and cryogenic (liquid nitrogen) temperatures, of four different epoxy systems that are used in high-field superconducting magnets, with the emphasis on rate-dependent plasticity as measured by uniaxial compression testing. As expected, both the elastic and plastic behaviour of the epoxy systems at room temperature depend strongly on their distance to the glass transition temperature, but become similar at cryogenic temperature. The rate dependency of the yield stress at room temperature of the four epoxy systems was similar and is well described by the Eyring model. At cryogenic temperatures the rate dependency disappears and the yield stress of all four epoxy systems approach a similar athermal value. The fracture toughness remained equal or even increased upon cooling to cryogenic temperatures for each of the four epoxies. However, the fracture toughness values of the four epoxies tested were quite different from each other, suggesting that fracture toughness not only depends on the van der Waals interactions between the segments but is also determined by other molecular characteristics, such as the network structure.